2021
DOI: 10.3390/plants10081500
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Wheat Fungi Diseases Identification by Deep Learning

Abstract: Diseases of cereals caused by pathogenic fungi can significantly reduce crop yields. Many cultures are exposed to them. The disease is difficult to control on a large scale; thus, one of the relevant approaches is the crop field monitoring, which helps to identify the disease at an early stage and take measures to prevent its spread. One of the effective control methods is disease identification based on the analysis of digital images, with the possibility of obtaining them in field conditions, using mobile de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…We conclude that CNNs must be applied carefully, especially when biological context is important. In contrast to similar plant classification approaches such as [7,9,19,20] our method initially extracts regions of interest learned from the images. These regions were used for classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that CNNs must be applied carefully, especially when biological context is important. In contrast to similar plant classification approaches such as [7,9,19,20] our method initially extracts regions of interest learned from the images. These regions were used for classification.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of plant identification studies is done by computer vision experts and a lack in interdisciplinary work [18]. In the recent plant science studies [19,20], the authors showed that explanatory factor extraction can be used for reliability investigation. Nevertheless, recent progress in the machine learning community showed, that CNNs may use image regions that happened to be related to the classification goal without any reasonable context, the so-called "clever-Hans phenomenon" [21].…”
Section: Introductionmentioning
confidence: 99%
“…The deep-learning network has been used extensively as part of the automated decision-making tool by extracting hierarchical features from input data for various agricultural tasks. As a result, this wide adoption of DL has opened new possibilities for interpreting massive amounts of data accurately for agriculture analytic systems, such as: Crop surveillance systems through remote sensing to map the land cover and crop discrimination [ 68 , 69 , 70 ]; Plant-stress-monitoring systems by implementing classification and segmentation networks to better understand the interactions between pathogens, insects, and plants, as well as to determine the causes of plant stress [ 71 , 72 , 73 , 74 , 75 ]; Disease and pest identification and quantification systems that will assist in monitoring the health condition of plants, including the nutritional status, development phase, and yield prediction [ 72 , 76 , 77 , 78 , 79 ]. …”
Section: Application Of Multiscale Deep Learningmentioning
confidence: 99%
“…Disease and pest identification and quantification systems that will assist in monitoring the health condition of plants, including the nutritional status, development phase, and yield prediction [ 72 , 76 , 77 , 78 , 79 ].…”
Section: Application Of Multiscale Deep Learningmentioning
confidence: 99%
“…Convolutional neural networks (CNNs), an important subset of machine learning techniques that learn hierarchical representations and discover potentially complex patterns from the data, have made impressive advances in the computer vision field [ 4 ]. CNNs have also yielded encouraging results in agriculture [ 5 ]. Although the approaches based on traditional machine learning techniques and deep learning techniques have achieved significant success in agricultural applications, developing lightweight networks for selective harvesting robots under unstructured environments is still difficult.…”
Section: Introductionmentioning
confidence: 99%